Redefining loyalism, radicalism and national identity - Navickas, K; Navickas, Katrina (2005)
﻿ Lancashire redefined popular politics and national identity in its own image. The perceived threat of invasion by Napoleon, together with the Irish Rebellion, sustained the evolution in extra-parliamentary politics that had begun in reaction to the American and French revolutions. The meanings and principles of 'radicalism,' 'loyalism' and 'Britain' continued to be debated and contested in 1798-1812. Elite loyalism became even more exclusive, developing into the Orange movement. Radicals remained silent until the Napoleonic invasion scares had faded and opportunities arose for renewed vocal criticisms of government foreign and economic policy from 1806. Conflicts re- emerged between radicals and loyalists in the middle classes and gentry which provided the training for a new generation of postwar radical leaders and the popularity of the free trade campaign. Inhabitants of Lancashire felt British in reaction to the French and Irish, but it was a Lancashire Britishness. Political identities and actions followed national patterns of events but were always marked with a regional stamp. This was in part because most political movements were held together by a shared 'sense of place' rather than vague notions of class-consciousness or shared class identity. A sense of place manifested itself in the regional organisation of strikes, petitions and the Orange institution. Furthermore, it could also entail a common bitter or defiant provincialism against the government or monarchy. In an atmosphere of anti-corruption and a growing desire for peace, this provincial frustration ironically brought professed loyalists closer to radicalism in campaigns against the Orders in Council and other government policies. Provincialism and other elements of regional identity ensured that any ideas of Britishness were tempered through local concerns and allegiances, but an identity with the nation that was not an acquiescent acceptance of national tropes and stereotypes. Lancashire Britishness was commercial, manufacturing, and above all, independent from homogenisation and the impositions of government.